Standardization Of The Recipe For Randang Daging As Traditional Food In Nagari Tapakis - Mifathul Nurul Huda; Elida Elida (Universitas Negeri Padang, 2021)
This study aims to standardie the recipe for meat randang as traditional food in Nagari Tapakis both in terms of ingredients, seasonings, and processing methods. The differences in ingradients, seasonings and processing methods make the result or quality of the meat range vary in terms of shape, aroma, texture and taste. This type of research is using a mixed method. This research was conducted in Nagari Tapakis, Ulakan Tapakis District, Padang Pariaman Regency. There are two data sources, quantitative, namely 10 trained panelists who know about randang and 5 limited panelists, namely a lecturer in Family Welfare Science, Faculty of Hospitality Tourism, Padang State University The qualitative data collection technique is the organoleptic tets questionnaire format.the results of the organoleptic tets for the meat randang recipe were a fairly square shape, the color of the meat and the randang bran was quite blackish brown, the texture oh the meat was quite soft, the texture of the randang bran was quite dry and oily, the taste of the meat was pervasive and the taste of the randang bran was savory